Investigations on PAHs and trace elements in coal and its combustion residues from a power plant. (15th December 2015) - Verma, S.K.; Masto, R.E.; Gautam, Shalini; Choudhury, D.P.; Ram, L.C.; Maiti, S.K.; Maity, Sudip
Highlights: PAHs and trace elements in coal and its ashes of a power plant were evaluated. ∑PAHs were higher in coal (4542 μg/kg) than combustion residues (10.6–32.5 μg/kg). Coal and fly ash have higher molecular weight PAHs; low molecular PAHs in bottom ash. As, Co, Cd are associated with P–Mg–Ca–S; Ni, V, Cu, Pb, Zn, Cr with Al–Si. Leaching of trace elements is within the permissible limit for industrial effluents. Abstract: Meeting the ever-growing demand of global energy in an eco-friendly manner necessitates the evaluation of coal and its combustion residues. For management of coal combustion and its residues on sustainable basis, characterization of trace elements and polycyclic aromatic hydrocarbons (PAHs) is imperative. The feed coal, fly ash, and bottom ash from a power plant (Unchahar, India) were evaluated. Feed coal is low grade high volatile sub-bituminous. Quartz and kaolinite are the predominant minerals in the coal, whereas quartz, mullite, and anhydrite in the ashes. Si > Al > Fe > Ca are the major elements in coal and it ashes. As compared to coal, most of the elements are enriched in the ashes; especially As, Cu, Ni, Pb, and Zn are highly enriched (enrichment factor > 5.0) in fly ash. Cluster analysis showed that As, Co, and Cd are associated with the ash forming elements like P–Mg–Ca–S; Ni, V, Cu, Pb, Zn, and Cr with Al-silicate minerals. Leaching study revealed that the trace elements are within the permissible limits for industrial effluents. The total PAHs content was much higher in coal (4542 μg kg −1 ) than fly ash (32.4 μg kg −1 ) and bottom ash (10.1 μg kg −1 ). High molecular weight PAHs were predominant in coal and fly ash, low molecular weight PAHs in bottom ash.